2011
DOI: 10.1016/j.ophtha.2011.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc Edema, Globe Flattening, Choroidal Folds, and Hyperopic Shifts Observed in Astronauts after Long-duration Space Flight

Abstract: The authors have no proprietary or commercial interest in any of the materials discussed in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
650
1
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 589 publications
(680 citation statements)
references
References 47 publications
15
650
1
14
Order By: Relevance
“…1,13 Increased intracranial pressure, papilledema, globe flattening, dilated optic nerve sheaths, and visual disturbances have been described in both conditions (Table 2). 1,13,14 Although the etiologies of both conditions are unknown, researchers speculate that venous insufficiency or hypertension caused by cephalad fluid shifts during spaceflight are possible mechanisms for the VIIP syndrome in astronauts. Similarly, the pathophysiology of IIH is thought to be related to decreased CSF absorption at the arachnoid villi possibly due to venous-outflow obstruction.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…1,13 Increased intracranial pressure, papilledema, globe flattening, dilated optic nerve sheaths, and visual disturbances have been described in both conditions (Table 2). 1,13,14 Although the etiologies of both conditions are unknown, researchers speculate that venous insufficiency or hypertension caused by cephalad fluid shifts during spaceflight are possible mechanisms for the VIIP syndrome in astronauts. Similarly, the pathophysiology of IIH is thought to be related to decreased CSF absorption at the arachnoid villi possibly due to venous-outflow obstruction.…”
mentioning
confidence: 98%
“…In the VIIP syndrome, none of the astronauts with ocular changes presented with clinical symptoms typical of IIH, including chronic headaches, diplopia, or transient visual obscurations. 1 Moreover, while IIH is typically a syndrome of female patients with obesity, 14 VIIP is more common in male astronauts. 1 Similarly, in our study of structural brain changes associated with long-term bed rest, we found important structural differences in our subjects from those previously described in patients with IIH.…”
mentioning
confidence: 99%
“…For example, long-term exposure to a microgravity environment may simultaneously elevate ICP and IOP and cause visual impairment (Mader et al, 2011;Woo et al, 2012). During this condition, ICP and IOP are altered together.…”
Section: Introductionmentioning
confidence: 99%
“…As consequence, the optic nerve sheath distension, optic disc edema, vascular changes in the choroid and retina (eg., folds choroidal, thickening of the retinal fiber layer, cotton wool spots), "flattening" of the eyeball and a hyperopic shift have been described in several astronauts (3,8) . Still, a moderate acute IOP increase in the first moments in microgravity (probably due to congestion in the episcleral veins), followed by a steady IOP decrease were observed during longer periods under microgravity and in the post-flight evaluations (8,9) . On the other hand, these ocular changes displayed in microgravity conditions, and potentially related to increased ICP, could not be directly compared with similar terrestrial disorders, such as idiopathic intracranial hypertension, because some astronauts participating in long-term space flights have not reported any visual symptoms or showed any change in their ocular examinations.…”
mentioning
confidence: 99%
“…Thus, the neuroretinal-cerebrospinal fluid interface (including lamina cribrosa) could be affected by microgravity, due to the local "cul-de-sac" anatomy of the optic nerve head and the relative increased ICP transmitted to the eye by the subarachnoid space. As consequence, the optic nerve sheath distension, optic disc edema, vascular changes in the choroid and retina (eg., folds choroidal, thickening of the retinal fiber layer, cotton wool spots), "flattening" of the eyeball and a hyperopic shift have been described in several astronauts (3,8) . Still, a moderate acute IOP increase in the first moments in microgravity (probably due to congestion in the episcleral veins), followed by a steady IOP decrease were observed during longer periods under microgravity and in the post-flight evaluations (8,9) .…”
mentioning
confidence: 99%